A note on observations of southern right whales at Campbell Island, New Zealand - Stewart, R; Todd, B (J. Cetacean Res. Manage., 2020)
Southern right whales were observed at Campbell Island, in New Zealand’s sub-Antarctic ocean, over four field seasons (1983, 1994, 1995 and 1997). Whales were present in both the winter and autumn of 1994. An average of 7-21 whales were seen each season, with a maximum of 44 whales per day in July 1995. Individual whales were resighted in the area over periods of several days to two months. A change to shorter residence periods occurred between the early 1980s and 1990s. Some interchange occurs between Campbell Island and the Auckland Islands, with a recent decrease in number at the former and an increase at the latter.